From Desire to Decision: The Impact of Hedonic Motivation and Store Aesthetics on Impulse Purchases - Rahmawati, Elisa Diah; Suryadi, Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of hedonic shopping motivation and visual merchandising on impulse buying among customers of OH!SOME at Olympic Garden Mall, Malang City. Design/methodology/approach – This study employs a quantitative explanatory research design to analyze the causal relationships among hedonic shopping motivation, visual merchandising, and impulse buying. Data were collected from 150 respondents who were OH!SOME customers aged at least 17 years and had experienced impulse purchasing. A non-probability sampling method with purposive sampling technique was used. Primary data were obtained through a five-point Likert-scale questionnaire, supported by secondary data sources. The data were analyzed using multiple linear regression with validity, reliability, and classical assumption tests, and hypothesis testing was conducted using the t-test in IBM SPSS Statistics 30.0. Findings – The results show that both hedonic shopping motivation and visual merchandising have a positive and significant effect on impulse buying. These findings indicate that emotional shopping enjoyment and attractive store visual presentation play an important role in triggering unplanned purchasing behavior among retail consumers. Originality/value – This study contributes to retail marketing literature by providing empirical evidence on how hedonic motives and visual merchandising jointly shape impulse buying behavior in the Indonesian retail context. The findings offer strategic insights for retailers seeking to design store environments that enhance emotional engagement and drive unplanned purchases.